علاقة الوسط الأسري بالعنف لدى الأطفال - عبيدي، بدر الدين. قطاوي، السعيد (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة: تهدف دراستنا الحالية إلى الإجابة عن التساؤل العام: هل توجد علاقة بين الوسط الأسري والعنف لدى الأطفال؟ واعتمدنا على التساؤلات الفرعية التالية: - هل توجد علاقة بين التنشئة الأسرية والعنف لدى الأطفال؟ - هل توجد علاقة بين المستوى الاقتصادي للأسرة والعنف لدى الأطفال؟ - هل توجد علاقة بين المستوى الثقافي للأسرة والعنف لدى الأطفال؟ و جاءت الفرضية العامة و الفرضيات الفرعية كالتالي: توجد علاقة بين الوسط الأسري والعنف لدى الأطفال. توجد علاقة بين التنشئة الأسرية والعنف لدى الأطفال. توجد علاقة بين المستوى الاقتصادي للأسرة والعنف لدى الأطفال. توجد علاقة بين المستوى الثقافي للأسرة والعنف لدى الأطفال. ولاختبار صحة الفرضيات اعتمدنا على المنهج الوصفي باعتباره أقرب للدراسة،واختيرت العينة بالطريقة القصدية أو العمدية على70أسرة ببلدية الوادي، وقد اعتمدنا في جمع البيانات على أداة الاستبيان. وفي الأخير توصلت الدراسة للعديد من النتائج أهمها وجود علاقة بين الوسط الأسري والذي يتمثل في التنشئة الأسرية والمستوى الاقتصادي والثقافي للأسرة بالعنف لدى الأطفال، كما بينت الدراسة عدة سلوكات عنف لدى أطفال المبحوثين أهمها الضرب الصراخ، السب و الشتم، العض، رمي و تكسير الأشياء. Study summary Our study aims to answer the general question: is there a relationship between family and children violence? We have relied on the following sub-questions: Is there a relationship between family upbringing and violence in children? - Is there a relationship between the economic level of the family and violence in children? - Is there a relationship between the cultural level of the family and violence in children? The general hypothesis and sub-hypotheses are as follows: There is a relationship between family and violence in children. There is a link between family upbringing and violence in children There is a relationship between the economic level of the family and violence in children. There is a relationship between the cultural level of the family and violence in children. In order to test the validity of hypotheses, we relied on the descriptive approach as a closer study, and the sample was chosen by the intentional method on 70 families in El Oued commune, we have relied in data collection on the questionnaire tool. In the end, the study reached several results, the most important of which is the existence of a relationship between the family, which is the family formation and the economic and cultural level of the family with violence in children. The study also showed several violent behaviors among the studied children, including beatings, shouting, insulting, cursing, and breaking things.
دراسة ميدانية لأسر ببلدية الوادي
مذكرة ماستر علوم اجتماعية تخصص جريمة وإنحراف
Keywords: التنشئة الاجتماعية، العنف، الأسرة; Socialisation, violence, famille; Socialization, violence, family